Kinetic modelling for glycerolysis of palm olein - Yeoh, Chiou Moi; Siew, Wai Lin; Choong, Thomas Shean Yaw; Yunus, Robiah; Abdullah, Luqman Chuah (2010)
The application of the enzymatic technology is getting attention in the fats and oils industry. It is important to understand the glycerolysis mechanism. In this study, a commercial immobilized lipase (Lipozyme TL IM) was used to catalyze the glycerolysis reaction. The kinetics of enzymatic glycerolysis reaction between TAG and glycerol were successfully modelled using rate equation with unsteady-state assumption. Three models were proposed for the study, i.e. simple ternary model, simple ping-pong bi bi model and complex ping pong bi bi model. The reaction rate constant was determined by using non-linear regression and the sum of square errors were minimized. The simulation results showed that complex ping-pong bi bi model well described the glycerolysis reaction mechanism. This model could be used for predicting the appropriate conditions for the efficient production of the desired product.